OUHP: an optimized universal hairpin primer system for cost-effective and high-throughput RT-qPCR-based quantification of microRNA (miRNA) expression. Issue 4 (25th November 2021) - He, Fang; Ni, Na; Wang, Hao; Zeng, Zongyue; Zhao, Piao; Shi, Deyao; Xia, Yinglin; Chen, Connie; Hu, Daniel A; Qin, Kevin H; Wagstaff, William; Qin, David; et al.
Abstract: MicroRNAs (miRNAs or miRs) are single-stranded, ∼22-nucleotide noncoding RNAs that regulate many cellular processes. While numerous miRNA quantification technologies are available, a recent analysis of 12 commercial platforms revealed high variations in reproducibility, sensitivity, accuracy, specificity and concordance within and/or between platforms. Here, we developed a universal hairpin primer (UHP) system that negates the use of miRNA-specific hairpin primers (MsHPs) for quantitative reverse transcription PCR (RT-qPCR)-based miRNA quantification. Specifically, we analyzed four UHPs that share the same hairpin structure but are anchored with two, three, four and six degenerate nucleotides at 3′-ends (namely UHP2, UHP3, UHP4 and UHP6), and found that the four UHPs yielded robust RT products and quantified miRNAs with high efficiency. UHP-based RT-qPCR miRNA quantification was not affected by long transcripts. By analyzing 14 miRNAs, we demonstrated that UHP4 closely mimicked MsHPs in miRNA quantification. Fine-tuning experiments identified an optimized UHP (OUHP) mix with a molar composition of UHP2:UHP4:UHP6 = 8:1:1, which closely recapitulated MsHPs in miRNA quantification. Using synthetic LET7 isomiRs, we demonstrated that the OUHP-based qPCR system exhibited high specificity and sensitivity. Collectively, our results demonstrate that the OUHP system can serve as a reliable and cost-effective surrogate of MsHPs for RT-qPCR-based miRNA quantification for basic research and precision medicine.